Floristic composition and ecological parameters of weeds in corn (Zea mays L.), in Tosagua, Ecuador - Grijalva-Villamar, Diego; Vera-Calderón, José; Saldarriaga-Lucas, Veris; Constante-Tubay, Gonzalo; López-Alava, Geoconda; Vélez-Olmedo, Jefferson; Vélez-Zambrano, Sergio (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Corn is one of the most important species worldwide due to its uses for feeding humans and animals. In Ecuador, the province of Manabí is considered the area with the largest cultivated area nationwide. This work aimed to characterize weeds' floristic composition and predominance in El Junco, Tosagua corn production systems. To estimate the dominance of existing weeds, 10 farms were selected, where thirty random samplings were carried out for each farm using a 0.50 x 0.50 m quadrant. At each sampling point, the existing weeds and their respective identification were counted. In total 39 species were identified, 32 belonging to the Magnoliopsida class (dicotyledons) and 7 to the Liliopsida class (monocotyledons) and grouped into 16 botanical families. The families with the greatest representation were: Poaceae (25,06 %), Euphorbiaceae (18,61 %), Cyperaceae (14,79 %), Asteraceae (9,76 %) and Malvaceae (8,49 %). The most frequent species were Urochloa fasciculata, Euphorbia hirta, Cyperus rotundus, Cyanthillium cinereum, Richardia scabra, Corchorus hirtus and Alternanthera sp. The species U. fasciculata, E. hirta, and C. rotundus obtained the highest dominance values with 3.88, 3.49, and 3.03 % respectively. In this way, we concluded that the Poaceae family, presented the greatest number of weeds in the corn production systems in the El Junco locality. Adequate knowledge of the floristic composition of an agroecosystem will allow the development of appropriate weed management strategies in different commercial corn fields.